A Case of Solitary Kidney Atrophy Due to Primary Hyperparathyroidism: A Case Report. Issue 2 (January 2016) - Lin, Yu-Ting; Jiang, Jiunn-Song; Fang, Yu-Wei; Tsai, Ming-Hsien
Abstract : Abstract: Although primary hyperparathyroidism (PHPT) is asymptomatic in most patients, its main clinical manifestation is nephrolithiasis. In general, hypercalcemia would lead to unilateral renal stones, which may become bilateral over time. We present a rare case of a large unilateral asymptomatic ureteral stone in a patient with hypercalcemia secondary to PHPT, which eventually led to renal atrophy. The diagnosis of PHPT should be considered in patients with hypercalcemia and renal stones, as asymptomatic PHPT may result in a devastating renal outcome.